Adubação com torta de filtro e micronutrientes no plantio da cana-de-açúcar - Adorna, Jaqueline Cristiane [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Rossato, Otavio Bagiotto [UNESP] (FapUNIFESP (SciELO), 2013)
The response of sugarcane to application of micronutrients is still not very well known. In view of the need for this information, the aim of this study was to evaluate the application of the micronutrients Zn, Cu, Mn, Fe, B, and Mo to plant cane in three soils, with and without application of filter cake. This study consisted of three experiments performed in the State of São Paulo, Brazil, (in Igaraçu do Tiete, on an Oxisol; in Santa Maria da Serra, on an Entisol, both in the 2008/2009 growing season; and in Mirassol, on an Ultisol, in the 2009/2010 growing season) in a randomized block design with four replications with a 8 x 2 factorial combination of micronutrients (1 - no application/control, 2 - addition of Zn, 3 - addition of Cu, 4 - addition of Mn 5 - addition of Fe, 6 - addition of B, 7 - addition of Mo, 8 - Addition of Zn, Cu, Mn, Fe, B, and Mo) and filter cake (0 and 30 t ha-1 of filter cake) in the furrow at planting. The application of filter cake was more efficient than of Borax in raising leaf B concentration to sufficiency levels for sugarcane in the Entisol, and it increased mean stalk yield in the Oxisol. In areas without filter cake application, leaf concentrations were not affected by the application of Zn, Cu, Mn, Fe, B, and Mo in the furrow at planting; however, Zn and B induced an increase in stalk and sugar yield in micronutrient-poor sandy soil.
Fertilization with filter cake and micronutrients in plant cane
Keywords: B; Cu; Fe; Filter cake; Mn; Mo; Sacharum spp; Zn